RENAM - collaborative e-infrastructure for research and education in Moldova - Bostan, Ion; Secrieru, Grigore; Tighineanu, Ion; Bogatencov, Petru (2014 RoEduNet Conference 13th Edition: Networking in Education and Research Joint Event RENAM 8th Conference, 2014)
Development of National research and educational networking infrastructure and services is the basis of modern eInfrastructure components operation. The paper describes current state, development prospects of scientific computing infrastructures and their users' communities in Moldova. Computing infrastructures (Grid, HPC, Cloud, etc.) have becoming the backbone of those fields of science that require solving complex computational problems.